2017
DOI: 10.2196/mhealth.8534
|View full text |Cite
|
Sign up to set email alerts
|

Social Communication Coaching Smartglasses: Well Tolerated in a Diverse Sample of Children and Adults With Autism

Abstract: BackgroundAugmented reality (AR) smartglasses are an emerging technology that is under investigation as a social communication aid for children and adults with autism spectrum disorder (ASD) and as a research tool to aid with digital phenotyping. Tolerability of this wearable technology in people with ASD is an important area for research, especially as these individuals may experience sensory, cognitive, and attentional challenges.ObjectiveThe aim of this study was to assess the tolerability and usability of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
0
46
0
3
Order By: Relevance
“…4.2.1 Glasses. Keshav et al [41] accessed the tolerability and usability of Augmented Reality glasses for children and adults with autism while using a social coaching application to improve social communication skills. After conducting a usability study they found that 19 out of 21 participants were able to use the glasses for a whole 60 -90 minute long session and afterwards reported to feel comfortable using them.…”
Section: Children and Adultsmentioning
confidence: 99%
“…4.2.1 Glasses. Keshav et al [41] accessed the tolerability and usability of Augmented Reality glasses for children and adults with autism while using a social coaching application to improve social communication skills. After conducting a usability study they found that 19 out of 21 participants were able to use the glasses for a whole 60 -90 minute long session and afterwards reported to feel comfortable using them.…”
Section: Children and Adultsmentioning
confidence: 99%
“…Specialized smartglasses designed for socio-emotional learning have been found to be feasible [34], well tolerated [38], safe [39], and help reduce symptoms of autism [34,40] and attention deficit hyperactivity disorder [41]. Additionally, despite past negative perceptions and stigma associated with such devices, children with autism express a desire to use these socio-emotional assistive smartglasses technology in the classroom setting [42].…”
Section: Smartglasses In Classesmentioning
confidence: 99%
“…The Empowered Brain is a smartglasses-based social skills coaching tool [34,38]. The system has been developed as a digital platform that integrates specialized modules on smartglasses, companion apps on smartphones/tablets, and a web-based data portal ( Figure 1).…”
Section: The Technologymentioning
confidence: 99%
“…The Empowered Brain is a tool that provides socio-emotional coaching to children and adults with ASD (Keshav et al, 2017;Liu et al, 2017). The Empowered Brain consists of a smartglasses platform in combination with a series of software modules that focus on key coaching areas, such as improving attention to social cues, helping coach facial emotion recognition, and aiding in transitioning between different environments.…”
Section: The Empowered Brain Technology Platformmentioning
confidence: 99%